Servant Leadership and Organizational Culture on Organizational Citizenship Behavior: The Mediation Role of Job Satisfaction - Jufrizen Jufrizen; Hazmanan Khair; Anggita Dwi Kesuma; Maya Sari; Molana Malik Pandia (Universitas Mercu Buana, 2023)
Objectives: This study aims to examine the process of forming Organizational Citizenship Behavior (OCB) in employees. This study uses job satisfaction as a mediating variable to clarify the mechanism of the influence of servant leadership and organizational culture on Organizational Citizenship Behavior (OCB).Methodology: This study uses a causal type of research using a quantitative approach with a sample of 67 respondents who are employees of PT Pelabuhan Indonesia (Persero) Branch TPK Perawang Pekanbaru. To evaluate the seven hypotheses put out in this study, data was collected via interviews and a list of assertions, such as questionnaires and data analysis methods employing Partial Least Square (SmartPls).Findings: The results of this study indicate that servant leadership and organizational culture have a positive and significant effect on Job Satisfaction and Organizational Citizenship Behavior. Job satisfaction also plays a role in mediating the influence of servant leadership and organizational culture on Organizational Citizenship Behavior.Conclusion: This study examines how servant leadership and organizational culture influence employee job satisfaction and organizational citizenship behavior to achieve company goals. As a result, this condition is undoubtedly a source of concern for the company in terms of improving leadership and aligning all employees' perceptions of the organizational culture system that will be implemented in the company.